Circulating protein Z concentration, PROZ variants, and unexplained cerebral infarction in young and middle-aged adults - Zhang, Lili; Segal, Alan Z.; Leifer, Dana; Silverstein, Roy L.; Gerber, Linda M.; Devereux, Richard B.; Kizer, Jorge R. (Thrombosis and Haemostasis, 2017)
Protein Z (PZ) is a vitamin K–dependent plasma protein that exhibits both pro- and anticoagulant properties. Both low and high PZ levels have been linked to ischaemic stroke. Although PZ-lowering gene variants have been found to be less common in ischaemic stroke, the relationship remains unclear. We investigated PZ levels and PROZ variants in a multi-ethnic case-control study of unexplained stroke in participants aged 18 to 64. Plasma PZ was measured in cases (≥2 months post-stroke) and controls. PZ polymorphisms G79A (rs3024735) and A13G (2273971) were genotyped. A combined genetic score (0–4 minor alleles) was created assuming additive effects. A total of 715 individuals (1:1.4 cases:controls) was included. Analyses revealed evidence of a non-linear association. After adjusting for demographic and clinical covariates, PZ levels >2.5 µg/ml (90th %ile) were significantly associated with cryptogenic stroke (OR 2.41 [95 % CI 1.34, 4.34]) as compared with lower levels. Higher genetic score was related to progressively lower levels of PZ, and the presence of four minor alleles was associated with lower odds of stroke (adjusted OR 0.26 [95 % CI 0.07, 0.96]) versus 0 minor alleles. In this multi-ethnic study of young and middle-aged adults, there was evidence of a nonlinear positive association between PZ level and unexplained stroke, with a directionally consistent association for genetic variants related to PZ levels and cryptogenic stroke. These findings support elevated PZ levels as a risk factor for cryptogenic stroke.
Keywords: Biomarkers; genetic association studies; plasma protein Z; risk factors; stroke